2014
DOI: 10.1093/ntr/ntu103
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Users' Interest in Using or Switching to Electronic Nicotine Delivery Systems for Smokeless Tobacco for Harm Reduction, Cessation, or Novelty: A Cross-Sectional Survey of US Adults

Abstract: Introduction: We examined: (a) current (past 30-day) smokers' interest in using or switching to electronic nicotine delivery systems (ENDS) or smokeless tobacco for various reasons; (b) correlates of interest in these products; and (c) subgroups of current smokers in relation to interest in these products. Methods: We conducted a cross-sectional survey assessing sociodemographics, tobacco use, interest in ENDS and smokeless tobacco among smokers, and knowledge about ENDS among 2,501 US adults recruited through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 46 publications
(49 reference statements)
13
89
2
2
Order By: Relevance
“…7 Our analyses add to the previous research by providing an examination of the reasons for use of e-cigarettes, and the impact of stated reasons on current tobacco use and intentions to quit. 25 Similar to prior research, 4,7,[14][15][16]25,26 we observed that the vast majority of smokers endorsed reasons for e-cigarette use related to quitting and reducing, and reduction in health risks. Results of our multivariable logistic regression analyses point to use of e-cigarettes as a means to quit smoking and to reduce stress as reasons that are independently associated with both intention to quit smoking and reduced use of cigarettes.…”
Section: Discussionsupporting
confidence: 84%
“…7 Our analyses add to the previous research by providing an examination of the reasons for use of e-cigarettes, and the impact of stated reasons on current tobacco use and intentions to quit. 25 Similar to prior research, 4,7,[14][15][16]25,26 we observed that the vast majority of smokers endorsed reasons for e-cigarette use related to quitting and reducing, and reduction in health risks. Results of our multivariable logistic regression analyses point to use of e-cigarettes as a means to quit smoking and to reduce stress as reasons that are independently associated with both intention to quit smoking and reduced use of cigarettes.…”
Section: Discussionsupporting
confidence: 84%
“…(Check all that apply. )” Response options were based on prior research (Berg, Barr et al 2014, Berg, Escoffery et al 2014). See Tables 3 and 4 for response options.…”
Section: Methodsmentioning
confidence: 99%
“…3 11 The most significant factor drawing smokers to e-cigarettes is their potential as a harm reduction or smoking cessation device. 8 The routes that cigarette smokers take to using ecigarettes are informal, however. A number of characteristics of e-cigarettes may be involved in smokers trying and adopting e-cigarettes.…”
Section: Introductionmentioning
confidence: 99%